The impact of AI on employment: a historical account of its evolution - Martha Garcia-Murillo; Ian MacInnes (International Telecommunications Society (ITS), 2019)
Artificial Intelligence (AI) is likely to have a significant impact on work. Examples from the past demonstrate that it has created jobs but also displaced workers. The primary question this study aims to answer is what have been the effects that previous revolutionary computing technologies have had and how have institutional values shaped the way workers were affected. The paper involves a historical analysis of the experiences that society in the United States has had with technological innovation. The research relies on academic, government, and trade publications of earlier periods in the development of computer technology. In this effort, we examine the literature on institutional economics to help us understand the way society has transitioned and the forces that have shaped the outcomes. Institutional economics has two main branches that explain change: the ceremonial and the instrumental. The ceremonial values perspective focuses on the customs and conventions that prevail in a community. The instrumental perspective focuses on a society's processes of inquiry, acquisition of knowledge, and use of scientific inquiry to solve problems Our analysis suggests that in all of these periods initial implementations suffered from installation problems, system bugs, and troubleshooting frustrations that generated employment; however, as the technology improves, it is likely to enhance productivity, but displace, workers. Up to this point, the U.S. government has not been able to respond adequately to the challenge. We attribute this to the ceremonial values that public officials and society entertain about personal responsibility and small government.
Keywords: 330; Artificial intelligence (AI); Technological displacement; Economic transition; Ceremonial values; Instrumental values; Public policy